2022
DOI: 10.3390/v14050948
|View full text |Cite
|
Sign up to set email alerts
|

Beta HPV Deregulates Double-Strand Break Repair

Abstract: Beta human papillomavirus (beta HPV) infections are common in adults. Certain types of beta HPVs are associated with nonmelanoma skin cancer (NMSC) in immunocompromised individuals. However, whether beta HPV infections promote NMSC in the immunocompetent population is unclear. They have been hypothesized to increase genomic instability stemming from ultraviolet light exposure by disrupting DNA damage responses. Implicit in this hypothesis is that the virus encodes one or more proteins that impair DNA repair si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Resulting hyperproliferative epithelium can form papillomas and represents a resource of new virus progeny. 21 In conjunction with chronic UV-exposure, however, cutaneous PVs interfere with DNA repair, 54,55 favoring the accumulation of driver mutations, for example, in the p53 gene, 14 that apparently results in both favoring the outgrowth of cells with a pathophysiological network counterselective for viral replication and making viral gene expression dispensable (Figures 2A and 3B).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting hyperproliferative epithelium can form papillomas and represents a resource of new virus progeny. 21 In conjunction with chronic UV-exposure, however, cutaneous PVs interfere with DNA repair, 54,55 favoring the accumulation of driver mutations, for example, in the p53 gene, 14 that apparently results in both favoring the outgrowth of cells with a pathophysiological network counterselective for viral replication and making viral gene expression dispensable (Figures 2A and 3B).…”
Section: Discussionmentioning
confidence: 99%
“…However, because NHEJ generates and ligates blunt ends to fix a DSB, it is more mutagenic than HR (Mao et al, 2008). We have shown that 8E6 attenuates both HR and NHEJ by degrading p300 (Hu et al, 2020; Hu and Wallace, 2022; Wallace et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Betapapillomavirus infection have been found to disrupt the two primary DSB repair pathways that is HR and C-NHEJ. 101 However, it was found that HPV E6 proteins, specifically HPV5, 8, and 38, decrease HR efficiency. Mechanistically, they downregulate the transcription regulator p300, resulting in decreased expression of BRCA1, BRCA2, and ATM, as well as reduced the formation of BRCA1 and BRCA2 repair complexes.…”
Section: Non-alpha Papillomaviruses and Microhomology-mediated Dna Re...mentioning
confidence: 99%
“…These effects are closely linked with HPV8 E6-dependant destabilization of p300, while the formation of XRCC4 foci is decreased independently of p300 destabilization. 101 By utilizing small molecule inhibitors, CRISPR/CAS9 gene knockout, and an HPV8 E6 mutant as model systems, researchers discovered that HPV8 E6 fosters MMEJ through its interaction with p300. As part of its repair pathway, MMEJ employs POLQ end joining.…”
Section: Non-alpha Papillomaviruses and Microhomology-mediated Dna Re...mentioning
confidence: 99%
See 1 more Smart Citation